Mechanical efficiency in baseball pitching - Fortenbaugh, D.; Fleisig, G. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Efficient pitching mechanics should maximize ball velocity while minimizing stress on the pitching arm. The purpose of this study was to quantify the relationship between ball velocity and upper extremity kinetics (UEKs) and define the kinematic patterns that achieve the most efficient pitching mechanics. Healthy collegiate and professional pitchers (n=147) threw maximal effort pitches from the wind-up. After determining the overall relationship between ball velocities and UEKs, two subgroups of pitchers were identified as efficient and inefficient. Efficient pitchers had significantly more ball velocity and similar or lower kinetic values. 10 of 23 kinematic variables were significantly different between the groups. It is recommended that coaches and researchers use the efficient group`s mechanics as a point of reference when analyzing and teaching pitching biomechanics.